Medical Student’s Perception About The Integrating Methods Of learning Medical Subjects And Importance Of Psychiatry In Pre-Clinical, Para-Clinical And Clinical Learning - Pandey, AK; Sapkota, N; Nivedita, Dr (Journal of Psychiatrists’ Association of Nepal, 2014)
Background: Now a day’s important elements being planned and used in the curriculum is vertical integration, i.e. integration between the clinical and basic science sections of the curriculum, and horizontal integration i.e. between different subject areas. Integration throughout the whole curriculum is time-consuming for both teachers and students and hard work is required for planning, organization and execution. Psychiatry is an important subject in medical sciences and knowledge of this subject is helpful in understanding function of body, mind and related issues which are modified by disease processes. Aim of the study is to assess the importance of horizontal and vertical integration in an undergraduate medical curriculum and importance of Psychiatry in pre-clinical, para-clinical and clinical learning, according to opinion among fourth year MBBS students. Methods and materials: A self administered questionnaire was used among all the consenting 4th Year MBBS Students of BPKIHS, Dharan, Nepal (324 of 400 responded) of four consecutive years to know about the importance of psychiatry as a subject and different components of the undergraduate medical curriculum including vertical and horizontal integration. They were asked to assign between three options to each question (from agree, neutral and disagree). Results: The result showed that majority of the students were in favor of vertical integration of the various subjects and admitted the importance of psychiatry as a subject and its knowledge helps them in better understanding of the other subjects included in medical curriculum. Conclusions: Vertical integration of medical subjects may be better than horizontal Integration for teaching and learning as this help students to understand the medical subject’s in a superior way. This study also reveals that as of its importance in the medical curriculum, subject of Psychiatry should be given more emphasis during the undergraduate training period. DOI: http://dx.doi.org/10.3126/jpan.v3i1.11346 J Psychiatrists’ Association of Nepal Vol .3, No.1, 2014: 10-15